A repeated flex fatigue resistant transmission belt adhesive and a preparation method thereof
Patent Information
- Application Number
- CN202611261481.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明针对现有氯丁胶传动带底胶反复屈挠疲劳寿命短、易龟裂失效的技术缺陷,提供一种耐反复屈挠疲劳传动胶带底胶配方及其制备方法
本发明通过炭黑N330与白炭黑的特定比例复配补强体系与抗屈挠龟裂助剂PL-6000的协同作用,使底胶的耐反复屈挠疲劳性能发生质的飞跃。依据GB/T13934-2006标准测试,本发明实施例在常温10万次反复屈挠后龟裂等级为0级,无龟裂、无开裂、无掉块;而传统氯丁底胶在3.2万次即出现微裂纹、10万次后达到3级严重龟裂。本发明抗屈挠疲劳寿命相较传统氯丁底胶提升200%以上,相较已有白炭黑复配方案提升100%以上,彻底解决了传动带底胶高频屈挠下早期龟裂失效的行业痛点。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of transmission belt base adhesive technology, specifically to a transmission belt base adhesive resistant to repeated flexural fatigue and its preparation method. Background Technology
[0002] The bottom rubber of the transmission belt is the core structural layer that bears the dynamic bending, compression rebound and stress transmission of the transmission belt. Its resistance to flexural fatigue directly determines the service life of the transmission belt.
[0003] In agricultural machinery operations and continuous industrial transmission conditions, the transmission belt needs to undergo dozens of repeated bending and flexing per minute. Under long-term alternating stress, conventional base rubber is prone to fatigue failure problems such as the initiation of internal micro-cracks, crack propagation, rubber layer cracking, localized chipping, and compression collapse, leading to transmission belt pitch misalignment, slippage failure, and breakage.
[0004] Existing formulations for chloroprene rubber used in transmission belts have significant drawbacks: conventional chloroprene rubber formulations suffer from uneven filler dispersion, poor crosslinking network stability, weak resistance to dynamic fatigue deformation, and crude preparation process parameters. These factors, such as internal bubbles and uneven crosslinking, easily lead to defects during mixing and vulcanization, further reducing the flexural durability of the rubber compound. Furthermore, the industry lacks specific preparation processes and standardized testing methods for the flexural fatigue performance of chloroprene rubber base layers, making it impossible to accurately control the long-term performance of the product.
[0005] To address the aforementioned issues, existing technologies have attempted to improve the performance of chloroprene rubber primers by adding short fibers and nano-montmorillonite. However, while short fiber modification can increase strength, it often leads to increased rigidity and decreased flexibility of the rubber compound, which is detrimental to fatigue life under high-frequency flexural conditions. Other technologies focus on improving heat resistance, but their improvement on repeated flexural fatigue performance is limited. Therefore, we propose a transmission belt primer resistant to repeated flexural fatigue and its preparation method. Summary of the Invention
[0006] This invention addresses the technical shortcomings of existing chloroprene rubber transmission belt base rubbers, such as short flexural fatigue life and susceptibility to cracking failure, by providing a flexural fatigue resistant transmission belt base rubber formulation and its preparation method. Through optimizing the chloroprene rubber base formulation system and improving the preparation process, this invention achieves the technical effect of no cracking after 100,000 cycles of flexural fatigue at room temperature and maintaining excellent fatigue resistance even after high-temperature aging.
[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution: a transmission belt base adhesive resistant to repeated flexural fatigue, comprising, by weight, the following components: 100 parts of chloroprene rubber CR121, 35-45 parts of high abrasion-resistant carbon black N330, 10-20 parts of silica, 4-6 parts of zinc oxide, 3-5 parts of magnesium oxide, 0.8-1.5 parts of sulfur, 0.5-2 parts of stearic acid, 3-7 parts of aromatic softening oil, 1.0-2.0 parts of antioxidant 4020, 0.5-1.5 parts of antioxidant RD, 0.5-2 parts of dispersant, and 2-5 parts of anti-flexural cracking agent PL-6000.
[0008] Preferably, by weight, it is composed of the following components: 100 parts of chloroprene rubber CR121, 40 parts of high abrasion-resistant carbon black N330, 15 parts of silica, 5 parts of zinc oxide, 4 parts of magnesium oxide, 1.0 part of sulfur; 1 part of stearic acid, 5 parts of aromatic softening oil, 1.5 parts of antioxidant 4020, 1 part of antioxidant RD, 1 part of dispersant, and 3 parts of anti-flexural cracking agent PL-6000.
[0009] Preferably, the mass ratio of the high abrasion-resistant carbon black N330 to silica is 2 to 4:1.
[0010] Preferably, the mass ratio of antioxidant 4020 to antioxidant RD is 1 to 2:1.
[0011] Preferably, the total mass of high abrasion-resistant carbon black N330 and silica in the primer is 50-60 parts, and silica accounts for 20%-35% of the total mass of the reinforcing filler system.
[0012] Preferably, the mass ratio of the anti-flexural cracking agent PL-6000 to silica is 1:3 to 8.
[0013] This invention also proposes a method for preparing the aforementioned resistant to repeated flexural fatigue transmission belt base adhesive, comprising the following steps: Step (1) First stage of intensive mixing: put chloroprene rubber into a closed intensive mixer and plasticize at room temperature for 2 minutes; add stearic acid, dispersant and antioxidant in sequence and mix for 3 minutes; then add carbon black, silica and softening oil in batches and continue mixing for 6-8 minutes, controlling the intensive mixing temperature ≤110℃. Step (2) Second stage reinforcement mixing: Discharge the first stage of the mixed rubber compound and let it stand and cool to room temperature. Then put it back into the internal mixer, add zinc oxide and magnesium oxide, mix for 3 minutes, and discharge the rubber compound. Step (3) Thin sheeting: Put the mixed rubber compound into the open mill, adjust the roller gap to 1.5mm, and repeat the thin sheeting 6 times, and make triangular wraps and roll the rollers 3 times each; Step (4) Curing: After filming, let it stand at room temperature for 24 hours to cure; Step (5) Compression vulcanization molding: Cut the cured rubber into shape and put it into a flat vulcanizing machine. The vulcanization temperature is 150-160℃, the vulcanization pressure is 15MPa, and the vulcanization time is 15-20min.
[0014] Preferably, the total duration of the mixing and kneading process in step (1) is 11 to 13 minutes.
[0015] Preferably, the vulcanization temperature in step (5) is 155°C and the vulcanization time is 18 min.
[0016] Preferably, in step (1) of the internal mixing process, carbon black and silica are added alternately in 2 to 3 batches, with an interval of 1 to 2 minutes between each batch.
[0017] Compared with the prior art, the present invention provides a transmission belt base adhesive resistant to repeated flexural fatigue and its preparation method, which has the following beneficial effects: This invention achieves a qualitative leap in the repeated flexural fatigue resistance of the base rubber through the synergistic effect of a specific ratio of carbon black N330 and silica reinforcing system and the anti-flexural cracking agent PL-6000. According to GB / T13934-2006 standard testing, the embodiment of this invention exhibits a crack level of 0 after 100,000 repeated flexural cycles at room temperature, with no cracking, splitting, or spalling; while traditional neoprene base rubber shows microcracks after 32,000 cycles and reaches severe cracking (level 3) after 100,000 cycles. The flexural fatigue life of this invention is more than 200% higher than that of traditional neoprene base rubber and more than 100% higher than existing silica compound solutions, completely solving the industry pain point of early cracking failure of transmission belt base rubber under high-frequency flexural stress.
[0018] This invention utilizes a synergistic protective system combining antioxidant 4020 and antioxidant RD, along with a stable cross-linked network structure, enabling the rubber compound to maintain excellent fatigue resistance even after thermo-oxidative aging at 120℃ for 72 hours. After aging, the tensile strength retention rate is ≥90.80%, and the elongation retention rate is ≥87.50%, with the surface remaining intact and crack-free after 100,000 flexural cycles. In contrast, traditional neoprene rubber retains only 76.20% of its tensile strength and 71.40% of its elongation after aging, exhibiting large-area cracking and localized spalling after 100,000 flexural cycles. The high-temperature aging fatigue resistance of this invention is significantly superior to existing technologies, making it particularly suitable for harsh working conditions such as continuous high temperatures and repeated bending, such as in agricultural machinery operations, and can greatly extend the service life of transmission belts in high-temperature environments.
[0019] This invention utilizes a flexible cross-linked network design with low constant elongation stress and high elongation to achieve excellent resilience stability of the rubber compound after repeated compression and bending. According to GB / T7759 standard testing, the compression set of the embodiments of this invention is 10.80%–11.20%, while that of traditional neoprene rubber is 18.50%, a reduction of over 40%. This significant reduction in compression set means that the transmission belt is less prone to compression collapse and permanent deformation under long-term alternating stress, fundamentally ensuring the pitch stability and power transmission accuracy of the transmission belt.
[0020] This invention is the first to use a specific ratio of 40 parts carbon black N330 and 15 parts silica in the base rubber of chloroprene rubber transmission belts, achieving a synergistic effect of rigid reinforcement and flexible toughening. Carbon black N330 provides high-strength skeletal support, while silica provides a flexible buffer layer and reduces dynamic heat generation. The combination of the two also avoids the problem of excessive rigidity and brittleness caused by using only carbon black filler. Compared with a single carbon black reinforcement scheme, this invention increases tensile strength by 18% and elongation at break by 14%. Compared with a scheme using insufficient silica, this invention reduces the flexural cracking grade from level 2 to level 0, achieving simultaneous optimization of strength and flexibility.
[0021] This invention employs a proprietary process system: low-temperature intensive mixing (≤110℃), followed by six passes through a 1.5mm thin tube, 24-hour curing, and 155℃×18-min compression molding vulcanization. This system ensures the performance of the rubber compound from the source of processing. Low-temperature mixing prevents the degradation of chloroprene rubber due to high-temperature dechlorination; multiple passes through a thin tube thoroughly eliminate internal air bubbles and filler agglomeration, preventing localized stress concentration during flexural processes; and 24-hour curing releases internal mechanical stress and stabilizes the molecular conformation. This process plays a crucial role in ensuring the final resistance to flexural fatigue.
[0022] This invention focuses on improving flexural fatigue performance while also optimizing a balance of various physical and mechanical properties, including hardness, tensile strength, elongation at break, and stress at 300% constant elongation. The compound possesses sufficient structural strength to withstand transmitted stress, as well as excellent flexibility to buffer dynamic bending impacts. Furthermore, it exhibits good processing fluidity, high filler dispersion, and uniform vulcanization crosslinking. Detailed Implementation
[0023] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0024] All raw materials used in this invention are commercially available industrial products, requiring no special customization or processing. The raw materials are widely available, with a stable supply, and have good industrial availability. The production and testing equipment used are all general-purpose equipment used in the rubber processing industry, requiring no import or special customization. They can be directly applied to existing rubber product production lines, demonstrating good feasibility for industrial transformation.
[0025] This invention addresses the technical defect of chloroprene rubber transmission belt base rubber being prone to fatigue cracks under repeated flexing conditions by systematically designing the formulation from three dimensions: optimization of the reinforcing filler system, regulation of the crosslinking network structure, and construction of an anti-fatigue protection system.
[0026] (I) Basis for selecting the main rubber Chloroprene rubber CR121 is a polar rubber with a predominantly 1,4-trans structure. The presence of chlorine atoms in its molecular chain endows it with excellent oil resistance, heat resistance, and ozone resistance. CR121 chloroprene rubber has a moderate molecular weight distribution and Mooney viscosity. During dynamic flexural deformation, it exhibits moderate resistance to molecular chain slippage, preventing both irreversible deformation due to excessive slippage and stress concentration due to excessive molecular chain rigidity. This makes it a key raw rubber choice that provides a fundamental guarantee for flexural fatigue resistance.
[0027] (II) Synergistic reinforcement mechanism of the reinforcing filling system The present invention adopts a reinforcing filler system of high abrasion resistant carbon black N330 and silica compound, wherein N330 is 40 parts and silica is 15 parts, with a mass ratio of 2.67:1.
[0028] Carbon black N330 is a high-abrasion-resistant furnace-processed carbon black with moderate particle size and structure. It can form physical adsorption and chemical bonding with rubber molecular chains, significantly improving the tensile strength and abrasion resistance of rubber compounds. However, rubber compounds reinforced with carbon black alone have problems such as excessive rigidity and high dynamic heat generation. During repeated flexing, stress concentration can accelerate crack initiation.
[0029] Silica (precipitated hydrated silica) contains abundant silanol groups (Si-OH) on its surface, which can form hydrogen bonds with polar groups on the chloroprene rubber molecular chains, creating a secondary network structure within the rubber matrix. Studies have shown that in reinforcing systems, increasing the amount of silica extends the fatigue life of the rubber compound, reduces internal potential defects, and slows crack propagation. The addition of silica can also reduce the dynamic heat generation of the rubber compound and improve its flexibility.
[0030] This invention blends N330 carbon black and silica in a specific ratio, achieving a synergistic effect of "rigid reinforcement plus flexible toughening": carbon black provides high-strength skeletal support, while silica provides a flexible buffer layer. Together, they construct a dense yet flexible filler network, effectively suppressing the generation and propagation of microcracks during flexure. Simultaneously, the blended filler avoids the problems of excessive rigidity and brittleness in the compound caused by using only carbon black filler.
[0031] (III) Design of vulcanization system and regulation of cross-linking network The vulcanization of chloroprene rubber differs from that of general diene rubber; its crosslinking reaction is mainly achieved through the reaction of metal oxides with the active chlorine atoms on the molecular chain. This invention employs a proprietary vulcanization activation system consisting of 5 parts zinc oxide, 4 parts magnesium oxide, and 1.0 part sulfur.
[0032] The vulcanization mechanism is as follows: After electron transfer occurs between the 1,2-allyl chloride in the chloroprene rubber molecular chain and the adjacent double bond, the active chlorine reacts with zinc oxide to form ether-type crosslinking bonds (—C—O—Zn—O—C—), achieving chemical crosslinking between molecular chains. Magnesium oxide also has an acid-absorbing function during vulcanization, absorbing the HCl generated in the reaction and preventing early scorching and gelation of the rubber compound.
[0033] The optimal ratio of zinc oxide to magnesium oxide is 5:4. Using zinc oxide alone easily leads to scorching, while using magnesium oxide alone results in a slow vulcanization rate. This invention strictly adheres to the 5:4 ratio (5 parts zinc oxide, 4 parts magnesium oxide), with a small amount of sulfur added to further adjust the crosslinking density and crosslink bond type, constructing a uniform and stable three-dimensional crosslinking network. This crosslinking network ensures both the bonding strength between molecular chains and retains a certain degree of freedom of molecular chain movement, significantly reducing the probability of crosslink breakage under repeated bending.
[0034] Studies have shown that while excessively high crosslinking density can increase tensile strength, it can also make the material brittle, reduce elongation at break, and cause cracks to propagate rapidly once formed. Conversely, while lower crosslinking density may sacrifice some strength, it allows for freer molecular chain movement, which helps alleviate stress concentration and improves flexural fatigue life. This invention achieves optimal crosslinking density design by precisely controlling the ratio of zinc oxide / magnesium oxide / sulfur.
[0035] (iv) Synergistic protection mechanism of anti-fatigue protection system This invention employs a compound anti-fatigue protection system consisting of 1.5 parts of antioxidant 4020 (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine), 1.0 part of antioxidant RD (2,2,4-trimethyl-1,2-dihydroquinoline polymer), and 3 parts of anti-flexural cracking agent PL-6000.
[0036] Antioxidant 4020 is a p-phenylenediamine-based antioxidant with excellent resistance to thermo-oxidative aging, ozone aging, and flexural cracking. It can capture peroxide free radicals generated during the thermo-oxidative aging of rubber, terminating the chain oxidation reaction. Antioxidant RD is a quinoline-based antioxidant with excellent thermal stability, suitable for long-term high-temperature aging conditions, and can form a synergistic effect with antioxidant 4020. The combination of the two can effectively inhibit the damage to the cross-linked network caused by thermo-oxidative aging during dynamic fatigue.
[0037] PL-6000, an anti-flexural cracking additive, is a specialized anti-fatigue functional additive. Its mechanism of action includes: improving the flexibility of molecular chain segments, lowering the glass transition temperature, and enabling the molecular chains to maintain mobility under low temperature and large deformation conditions; altering the stress distribution at the crack tip during flexural cycles, transforming linear microcracks into nonlinear bifurcation propagation or directional tearing, thereby significantly extending fatigue life; and synergistically working with antioxidants to inhibit free radical-induced oxidative cracking during flexural processes. The addition of PL-6000 is one of the core innovations of this invention. Its synergistic effect with silica (PL-6000 to silica mass ratio of 1:5) further enhances the resistance of the rubber compound to crack initiation and propagation.
[0038] (v) The process assurance role of the processing aid system One part stearic acid, acting as a processing aid and activator, reduces the viscosity of the rubber compound and improves filler dispersion. It also reacts with zinc oxide to form zinc stearate, promoting the vulcanization reaction. Five parts aromatic softening oil, acting as a plasticizer, improves the flexibility and processing fluidity of the rubber compound. However, this invention intentionally controls its dosage (lower than 7 parts in Comparative Example 1 and 6 parts in Comparative Example 2) to avoid excessive softening that leads to decreased compound strength and increased dynamic heat generation. One part dispersant improves the uniformity of carbon black and silica dispersion in the rubber matrix, preventing localized stress concentration caused by filler agglomeration.
[0039] Process principle and key parameter control of the preparation method This invention systematically solves the problems of uneven mixing, numerous internal defects, and unstable cross-linking of chloroprene rubber through a proprietary process of segmented intensive mixing, low-temperature thin-passing, and gradient vulcanization.
[0040] Step (1) Process control of one stage of intensive mixing Add 100 parts of chloroprene rubber to a closed internal mixer and plasticize at room temperature for 2 minutes to allow the rubber molecular chains to fully expand under mechanical shearing and reduce the elastic memory effect. Add stearic acid, dispersant, and antioxidant sequentially, and mix for 3 minutes to ensure that the small molecule additives preferentially contact the rubber molecular chains. Then add carbon black, silica, and softening oil in batches, and continue mixing for 6–8 minutes. The key control parameter is a mixing temperature ≤110℃.
[0041] The reason for temperature control is that chloroprene rubber molecules contain active chlorine atoms, which are prone to dehydrochlorination at high temperatures (>120℃), leading to crosslinking or degradation of the molecular chains. This not only affects the uniformity of crosslinking in the subsequent vulcanization process but also reduces the fatigue resistance of the rubber compound. This invention strictly controls the mixing temperature to ≤110℃, fundamentally avoiding irreversible damage to the rubber molecular structure caused by high-temperature mixing.
[0042] Carbon black and silica are added in batches, alternating between the two batches (2-3 batches, with an interval of 1-2 minutes between each batch) to avoid uneven packing dispersion and localized overheating caused by adding a large amount at once. Softening oil is added in the later stages of packing addition to act as a wetting and dispersing aid.
[0043] Step (2) Process control of two-stage reinforced compounding After the first stage of compounding is discharged and allowed to cool to room temperature, it is put back into the internal mixer, and vulcanization activators such as zinc oxide and magnesium oxide are added. The mixture is then mixed for 3 minutes. The purpose of the second stage of mixing is to prevent the vulcanization activators from being exposed to the high-temperature mixing environment too early, which could lead to premature cross-linking (scorching). At the same time, after the reinforcing fillers have been fully dispersed in the first stage, the addition of the vulcanization activators ensures that they are evenly distributed in the compound, avoiding fatigue performance degradation caused by uneven local cross-linking density.
[0044] Step (3) Process control of thin-walled wafer extrusion The mixed rubber compound is fed into an open mill, with the roll gap adjusted to 1.5 mm. It is then subjected to six thin passes, followed by three triangular passes and three roll rolls. The thin passes serve several purposes: utilizing the powerful shearing force of the open mill to further break up residual filler agglomerates; removing air bubbles trapped within the compound through repeated folding and rolling, thus eliminating internal defects; and promoting uniform mixing of the components at the microscale. Studies have shown that improved filler dispersion uniformity helps establish a uniform stress field, reduces energy concentration at crack tips, and improves flexural fatigue life. The triangular passes and roll rolls alter the stress direction of the rubber compound, achieving multi-dimensional homogenization.
[0045] Step (4) Process control of aging and maturation After sheeting, allow to stand at room temperature for 24 hours to mature. The purpose of maturation includes: releasing the mechanical stress introduced during mixing and thin-passing, preventing stress concentration that could lead to deformation cracking during subsequent vulcanization and use; allowing the rubber molecular chains to rearrange in a free state, stabilizing the molecular conformation; and allowing the compounding agents to further diffuse and migrate under room temperature conditions, achieving a more uniform microscopic distribution.
[0046] Step (5) Process control of compression molding and vulcanization The cured rubber compound is cut into shape and placed in a flat vulcanizing machine. The vulcanization temperature is 150-160℃, the vulcanization pressure is 15MPa, and the vulcanization time is 15-20min. The preferred vulcanization temperature is 155℃ and the vulcanization time is 18min.
[0047] The selection of vulcanization temperature needs to balance the vulcanization rate and crosslinking uniformity: if the temperature is too low (<150℃), the vulcanization speed will be slow and the production efficiency will be low; if the temperature is too high (>160℃), it may cause a large internal temperature gradient in the rubber compound, uneven crosslinking, and even lead to thermal oxidative degradation of the rubber molecular chains. The vulcanization time should be aimed at achieving positive vulcanization (T90). If it is too short, the crosslinking will be insufficient and the strength will be inadequate; if it is too long, it may lead to over-vulcanization, making the rubber compound brittle and reducing its flexural properties.
[0048] Example 1 Weigh the following components by weight: 100 parts of chloroprene rubber CR121; 40 parts of high abrasion-resistant carbon black N330; 15 parts of silica; 5 parts of zinc oxide; 4 parts of magnesium oxide; 1.0 part of sulfur; 1 part of stearic acid; 5 parts of aromatic softening oil; 1.5 parts of antioxidant 4020; 1 part of antioxidant RD; 1 part of dispersant; and 3 parts of anti-flexural cracking agent PL-6000.
[0049] Preparation method: (1) First stage of intensive mixing: 100 parts of chloroprene rubber were put into a closed intensive mixer and plasticized at room temperature (23±2℃) for 2 minutes with a rotor speed of 40r / min; stearic acid, dispersant and antioxidant were added in sequence and mixed for 3 minutes; carbon black N330 and silica were added in 3 batches alternately (each batch was about 1.5 minutes apart), and aromatic softening oil was added at the same time when the second batch was added. The mixing continued until the total time reached 11 minutes, and the intensive mixing temperature was controlled to be ≤110℃ (the actual peak temperature was 108℃). The rubber was then discharged. (2) Second stage reinforcement mixing: After the first stage of compound is discharged, it is spread on a metal tray and allowed to cool naturally to room temperature (about 25°C). Then it is put back into the internal mixer, zinc oxide and magnesium oxide are added, and it is mixed for 3 minutes. The temperature is controlled to be ≤100°C, and the compound is discharged. (3) Thin pass and sheeting: Put the mixed rubber into the open mill, adjust the roller gap to 1.5mm, control the roller temperature at 40-50℃, and repeat the thin pass 6 times. After each thin pass, fold the rubber sheet and rotate it 90° before putting it back in; after the thin pass is completed, make a triangular wrap 3 times and roll the roller 3 times. (4) Curing: After filming, let it stand at room temperature (23±2℃) for 24 hours to cure, and control the film thickness evenly at 6-8mm; (5) Compression vulcanization molding: Cut the cured rubber material into mold size, put it into a flat vulcanizing machine, vulcanization temperature 155℃, vulcanization pressure 15MPa, vulcanization time 18min, and after vulcanization, let it cool naturally to room temperature to obtain the flexural fatigue resistant transmission belt base rubber product.
[0050] Example 2 Weigh the following components by weight: 100 parts of chloroprene rubber CR121; 35 parts of high abrasion-resistant carbon black N330; 18 parts of silica; 4 parts of zinc oxide; 5 parts of magnesium oxide; 1.2 parts of sulfur; 1.5 parts of stearic acid; 4 parts of aromatic softening oil; 1.8 parts of antioxidant 4020; 1.2 parts of antioxidant RD; 1.5 parts of dispersant; and 4 parts of anti-flexural cracking agent PL-6000.
[0051] The preparation method is the same as in Example 1, except that the total duration of the first stage of intensive mixing is 12 min (2 min of plasticizing, 3 min of mixing with additives, and 7 min of mixing with fillers), the vulcanization temperature is 152℃, and the vulcanization time is 20 min.
[0052] Example 3 Weigh the following components by weight: 100 parts of chloroprene rubber CR121; 45 parts of high abrasion-resistant carbon black N330; 12 parts of silica; 6 parts of zinc oxide; 3 parts of magnesium oxide; 0.9 parts of sulfur; 0.8 parts of stearic acid; 6 parts of aromatic softening oil; 1.2 parts of antioxidant 4020; 0.8 parts of antioxidant RD; 0.8 parts of dispersant; and 2.5 parts of anti-flexural cracking agent PL-6000.
[0053] The preparation method is the same as in Example 1, except that the total duration of the first stage of intensive mixing is 13 min (2 min of plasticizing, 3 min of mixing with additives, and 8 min of mixing with fillers), the vulcanization temperature is 158℃, and the vulcanization time is 16 min.
[0054] Comparative Example 1 Weigh the following components by weight: 100 parts chloroprene rubber CR121; 48 parts high abrasion-resistant carbon black N330; 5 parts zinc oxide; 4 parts magnesium oxide; 1.0 part sulfur; 1 part stearic acid; 7 parts aromatic softening oil; 1.0 part antioxidant 4020; 0.5 parts antioxidant RD. No silica, dispersant, or flexural cracking agent PL-6000 is added.
[0055] The preparation method is the same as in Example 1.
[0056] Comparative Example 2 Weigh the following components by weight: 100 parts chloroprene rubber CR121; 45 parts high abrasion-resistant carbon black N330; 6 parts silica; 5 parts zinc oxide; 4 parts magnesium oxide; 1.0 part sulfur; 1 part stearic acid; 6 parts aromatic softening oil; 1.2 parts antioxidant 4020; 0.8 parts antioxidant RD; 0.5 parts dispersant. No flexural cracking agent PL-6000 is added.
[0057] The preparation method is the same as in Example 1.
[0058] Comparative Example 3 (a comparative example to further verify the effect of the anti-flexural agent) Weigh the following components by weight: 100 parts of chloroprene rubber CR121; 40 parts of high abrasion-resistant carbon black N330; 15 parts of silica; 5 parts of zinc oxide; 4 parts of magnesium oxide; 1.0 part of sulfur; 1 part of stearic acid; 5 parts of aromatic softening oil; 1.5 parts of antioxidant 4020; 1 part of antioxidant RD; and 1 part of dispersant. The anti-flexural cracking agent PL-6000 is not added; otherwise, it is the same as in Example 1.
[0059] The preparation method is the same as in Example 1. This comparative example was used to individually verify the effect of the anti-flexural cracking additive PL-6000 on improving flexural fatigue performance.
[0060] Comparative Example 4 (A comparative example to further verify the amount of silica used) The components were weighed according to the following parts by weight: 100 parts of chloroprene rubber CR121; 30 parts of high abrasion-resistant carbon black N330; 25 parts of silica; 5 parts of zinc oxide; 4 parts of magnesium oxide; 1.0 part of sulfur; 1 part of stearic acid; 5 parts of aromatic softening oil; 1.5 parts of antioxidant 4020; 1 part of antioxidant RD; 1 part of dispersant; and 3 parts of anti-flexural cracking agent PL-6000. The amount of silica exceeded the preferred range of this invention (10-20 parts), and other aspects were the same as in Example 1.
[0061] The preparation method is the same as in Example 1. This comparative example is used to verify the effect of the upper limit of silica content on the overall performance of the rubber compound.
[0062] Performance testing: Test method: All samples were prepared according to the above-described preparation process to create standard test specimens. Rubber test sheets with a thickness of 6 mm and flexural strip specimens (150 mm × 25 mm × 6 mm) were uniformly prepared according to GB / T2941 standard. After preparation, all samples were left to stand at room temperature (23 ± 2 ℃) for 24 hours to eliminate processing internal stress before being uniformly tested to ensure the uniqueness of experimental variables.
[0063] 1. Shore A hardness: According to GB / T531.1 standard, a Shore A hardness tester is used for testing. The sample thickness is not less than 6mm, and the average value is taken from 5 different locations.
[0064] 2. Tensile properties: According to GB / T528 standard, the specimens were cut with a type I dumbbell-shaped cutter and the tensile speed of the electronic universal tensile testing machine was 500 mm / min. The tensile strength, elongation at break and stress at 300% constant elongation were tested. At least 5 specimens were tested in each group and the average value was taken.
[0065] 3. Compression permanent deformation: According to GB / T7759.1 standard, type A specimens (diameter 29mm±0.5mm, height 12.5mm±0.5mm) were used, with a compression rate of 25%, a test temperature of 70℃±1℃, and a test time of 24h±0.5h. After unloading, the height change was measured after 30 minutes of recovery at room temperature.
[0066] 4. Repetitive flexural fatigue resistance: Based on GB / T13934-2006 "Determination of Flexural Cracking of Vulcanized Rubber", a Demosis rubber flexural cracking tester was used. The flexural frequency was set to 5Hz±0.2Hz, and the maximum stroke to 25mm±1mm. The specimen was a long strip (150mm×25mm×6mm) with no pre-cut in the middle (for determining flexural cracking performance). Continuous flexing was performed up to 100,000 cycles or until specimen failure. The surface cracking grade (0 for no cracking, 1 for slight cracking, 2 for significant cracking, and 3 for severe cracking) and crack length were observed and recorded. The critical number of flexural cycles for the first appearance of a microcrack, the appearance of a grade 1 crack, and the appearance of a grade 2 crack / fracture were also recorded.
[0067] 5. Aging and flexural resistance: The samples were placed in a thermo-oxidative aging chamber at 120℃±2℃ for 72h±0.5h, then removed and allowed to recover at room temperature for 24h. A flexural test of 100,000 cycles was then conducted again according to GB / T13934-2006 to test the fatigue resistance of the rubber compound after high-temperature aging. Simultaneously, the retention rate of tensile strength and elongation at break after aging was tested according to GB / T3512 standard.
[0068] Table 1 Comparison of Basic Physical Properties Analysis and Summary: Comparative Example 1 exhibited the highest hardness and greatest compression set, indicating high rigidity and poor resilience, which is the fundamental reason for its short flexural fatigue life. Comparative Example 2 showed some improvement compared to Comparative Example 1, but its compression set was still as high as 15.30%, indicating insufficient flexural fatigue performance. Comparative Example 3 showed improved tensile strength and elongation at break compared to Comparative Example 2, with compression set reduced to 14.80%, but still significantly higher than Example 1, demonstrating that the anti-flexural additive plays an irreplaceable role in reducing compression set and improving resilience. Comparative Example 4 had excessively high hardness and high 300% elongation stress, indicating excessive rigidity of the rubber compound, which is detrimental to flexural fatigue performance. Simultaneously, its tensile strength decreased, indicating that excessive silica leads to filler agglomeration and reduced reinforcing efficiency. In Examples 1-3 of this invention, the stress at a given elongation is appropriately reduced and the elongation at break is increased, resulting in greater flexibility and stronger stress buffering of the rubber compound, thereby fundamentally reducing the probability of flexural cracks. The compression set is significantly reduced to 10.80%-11.60%, which means that the compound does not collapse after repeated bending and is not prone to fatigue failure.
[0069] Table 2 Comparison of flexural crack life at room temperature Test standard: GB / T13934-2006; Test conditions: frequency 5Hz, stroke 25mm, continuous reciprocating flexion, room temperature (23±2℃).
[0070] Summary and Analysis: Comparative Example 1, using traditional single-carbon black reinforced neoprene primer, began to develop microcracks after 32,000 cycles, exhibited Grade 1 cracking at 48,000 cycles, Grade 2 cracking / scraping at 75,000 cycles, and reached Grade 3 severe cracking after 100,000 cycles, failing to meet the long-term use requirements of agricultural machinery drive belts. Comparative Example 2, although adding a small amount of silica and dispersant, delayed the initial microcracks to 51,000 cycles, but still reached Grade 2 cracking after 100,000 cycles, showing limited improvement in flexural fatigue performance. Comparative Example 3 delayed the initial microcracks to 78,000 cycles, exhibited Grade 1 cracking at 91,000 cycles, and remained at Grade 1 cracking after 100,000 cycles, indicating that optimizing the silica dosage was effective, but without the addition of an anti-flexural additive, it still could not meet the requirement of no cracking after 100,000 cycles. This comparison fully demonstrates the indispensability of the anti-flexural cracking additive PL-6000. Comparative Example 4 exhibited only 45,000 initial microcrack cycles, performing worse than Comparative Example 3. This demonstrates that more silica is not necessarily better; excessive silica can actually impair flexural fatigue performance due to filler agglomeration and increased rigidity of the compound. Examples 1-3 of this invention, through the synergistic effect of the optimal carbon black / silica ratio compound, anti-flexural additives, a low-oil flexibility system, and a highly dispersed system, achieved 100,000 cycles of high-frequency repeated flexing without any cracking, spalling, or surface damage. The anti-flexural fatigue performance was improved by over 200% compared to Comparative Example 1 and over 100% compared to Comparative Example 2.
[0071] Table 3 Comparison of flexural fatigue after thermal aging Pretreatment: thermo-oxidative aging at 120℃±2℃ for 72h±0.5h, followed by 100,000 flexural tests (according to GB / T13934-2006).
[0072] Analysis and Summary: Comparative Example 1, ordinary chloroprene rubber, after thermo-oxidative aging at 120℃ for 72 hours, showed significant damage to the cross-linking network and breakage of molecular chains, resulting in brittle rubber. The tensile strength retention rate was only 76.20%, and the elongation retention rate was only 71.40%. After 100,000 flexural cycles, large-area cracking and localized spalling occurred. Comparative Example 3, after aging, showed a tensile strength retention rate of 87.10% and an elongation retention rate of 83.20%, which was better than Comparative Examples 1 and 2. However, slight cracking still occurred after 100,000 flexural cycles, indicating that the lack of anti-flexural additives led to insufficient flexibility of the aged rubber. Examples 1-3 of this invention, with their compounded anti-aging system, stable cross-linking network, and anti-flexural additives, achieved a tensile strength retention rate ≥90.80% and an elongation retention rate ≥87.50% after high-temperature aging. After 100,000 flexural cycles, the surface remained intact without cracks, proving that the rubber of this invention maintains excellent fatigue resistance even after high-temperature aging, making it highly suitable for the harsh working conditions of agricultural machinery involving continuous high temperatures and repeated bending.
[0073] Comparing Comparative Example 3 and Example 1, both used 15 parts of silica, with other components being essentially the same. Comparative Example 3 showed initial microcracks at 78,000 cycles and a crack grade of 1 after 100,000 cycles; Example 1 showed no cracks after 1,000,000 cycles and a crack grade of 0. The addition of PL-6000 increased the flexural fatigue life from less than 100,000 cycles to over 100,000 cycles without cracking, and reduced the compression set from 14.80% to 11.20%, demonstrating the core contribution of the anti-flexural cracking additive.
[0074] Comparative Example 2 (6 parts silica), Example 1 (15 parts silica), and Comparative Example 4 (25 parts silica). When the silica content was increased from 6 parts to 15 parts, the initial microcrack count increased from 51,000 to >100,000 (Example 1); however, when the content was further increased to 25 parts, the initial microcrack count decreased to 45,000 (Comparative Example 4). This indicates that there is an optimal range for silica content (10-20 parts). Exceeding this range will impair flexural fatigue performance due to filler agglomeration and increased rigidity. The preferred silica content of 15 parts in this invention is the optimal value verified through systematic experiments.
[0075] Verification of the contribution of the preparation process: To verify the superiority of the preparation process of the present invention, the formulation of Example 1 was used, but the preparation process conditions were changed for comparison: Summary and Analysis: High-temperature mixing leads to thermal oxidative degradation and premature cross-linking of the chloroprene rubber molecular chains, resulting in grade 2 cracking after 100,000 flex cycles. Reducing the number of thin passes results in uneven filler dispersion and residual internal air bubbles, leading to grade 1 cracking after 100,000 flex cycles. This invention, through a proprietary process of low-temperature mixing, six thin passes, and 24-hour curing, ensures grade 0 cracking after 100,000 flex cycles, fully demonstrating the crucial role of the preparation process in guaranteeing the final performance.
[0076] The repetitive flexural fatigue resistant transmission belt base rubber prepared by this invention can be widely used in agricultural machinery transmission belts, such as the transmission systems of harvesters, tractors, seeders, and other agricultural machinery, as well as industrial V-belts, narrow V-belts, cut-edge V-belts, multi-ribbed belts, and synchronous belts. It is especially suitable for agricultural machinery transmission systems that operate under long-term high temperature, high load, and high frequency flexural conditions.
[0077] The raw materials used in this invention are all commercially available conventional rubber industrial raw materials. The preparation process uses general equipment in the rubber processing industry, requiring no special equipment investment. It can be directly mass-produced on existing rubber processing production lines and has good prospects for industrial promotion and application.
[0078] This invention is the first to use a specific blend ratio of 40 parts carbon black N330 and 15 parts silica in the base rubber of chloroprene rubber transmission belts. Utilizing the synergistic effect of the rigid reinforcement of carbon black and the flexible toughening effect of silica, a filler network combining rigidity and flexibility is constructed. Compared to existing technologies that rely on single carbon black reinforcement or insufficient silica content, this invention achieves a simultaneous increase in tensile strength (21.5 MPa) and elongation at break, while significantly reducing compression set to 11.20%. Silica / carbon black mixed fillers are an effective way to improve the dynamic properties of rubber materials.
[0079] This invention introduces PL-6000 (3 parts) as an anti-flexural cracking agent into the base rubber formulation of neoprene transmission belts for the first time, forming a synergistic effect with silica in a specific ratio (1:5). Comparative experiments between Comparative Example 3 and Example 1 demonstrate that the addition of PL-6000 reduces the flexural cracking grade from level 1 to level 0 after 100,000 cycles, and increases the elongation retention rate after aging from 83.20% to 88.30%, achieving a qualitative leap in flexural fatigue life.
[0080] Based on the metal oxide vulcanization mechanism of chloroprene rubber, this invention uses 5 parts zinc oxide, 4 parts magnesium oxide (optimal ratio of 5:4) and 1.0 part sulfur to construct a three-dimensional network structure with optimized crosslinking density, which maximizes the flexibility and fatigue resistance of molecular chains while ensuring strength.
[0081] This invention eliminates internal defects and stress concentration from the processing source through a three-stage process control (low-temperature mixing ≤110℃ → 1.5mm thin pass 6 times → 24h curing → 155℃×18min molding vulcanization). Process comparison experiments demonstrate that, compared to the control process of high-temperature mixing (130℃) and reduced thin pass (2 times), the flexural cracking grade of this invention is improved from level 2 and level 1 to level 0, respectively, fully demonstrating the crucial role of process parameters.
[0082] The rubber compound of this invention exhibits no cracking (grade 0) after 100,000 repeated flexing cycles at room temperature, which is more than two grades higher than Comparative Example 1 (grade 3 cracking). After thermo-oxidative aging at 120℃ for 72 hours, the tensile strength retention rate is ≥90.80%, and the elongation retention rate is ≥87.50%, with the surface remaining intact after 100,000 flexing cycles. This comprehensive performance level has not been reported in existing neoprene transmission belt base rubber technology, completely solving the industry pain points of traditional neoprene base rubber being prone to flexing cracking and rapid failure after high-temperature aging.
[0083] Material source and equipment description I. Main Raw Material Sources All raw materials used in this invention are commercially available materials commonly used in the rubber industry and can be obtained through the following channels, but are not limited to the listed suppliers: 1. Chloroprene rubber CR121 Chloroprene rubber CR121 is a general-purpose, vulcanized chloroprene rubber with excellent physical and mechanical properties, resistance to sunlight and ozone aging, weathering, chemical reagents, and oils. Major domestic manufacturers include Shanxi Shanna Synthetic Rubber Co., Ltd., Chongqing Changshou Chemical Co., Ltd., and Shanxi Huojia Changhua Synthetic Rubber Co., Ltd. The product appears as a milky white, beige, or light brown sheet or block solid with a density of 1.23–1.25 g / cm³. 3 Commercially available sizes are typically 25kg / piece.
[0084] 2. High abrasion resistant carbon black N330 High abrasion-resistant carbon black N330 (HAF) is the most widely used high abrasion-resistant carbon black, with an iodine absorption value of 82 g / kg and a DBP absorption value of 102 cm⁻¹. 3 / 100g, possessing both reinforcing and processing properties. With a particle size of 26-30nm, it belongs to hard carbon black, exhibiting excellent reinforcing and abrasion resistance. Product quality complies with GB3778-2011 "Carbon Black for Rubber". Major domestic manufacturers include Tianjin Tianhao Carbon Black Co., Ltd., Qingdao Jinzetai Chemical Co., Ltd., and Shanxi Hengda Chemical Co., Ltd.
[0085] 3. White carbon black (precipitated hydrated silica) Silica, or precipitated hydrated silica (SiO2·nH2O), is a white powder with good chemical stability and a large specific surface area, making it suitable for rubber reinforcement. Product quality conforms to the HG / T3061-2020 standard, "Precipitated Hydrated Silica in Rubber Compounding Agents." Major domestic manufacturers include Wuxi Hengcheng Silicon Industry Co., Ltd. (annual capacity of 115,000 tons), Zhuzhou Xinglong Chemical Industry Co., Ltd., and Shanghai Yuanjiang Chemical Co., Ltd.
[0086] 4. Zinc oxide Zinc oxide (ZnO) for the rubber industry is produced by either indirect or wet processes, with a content ≥99.7%, and is used as an activator for the vulcanization of chloroprene rubber. It conforms to the GB / T3185-2016 standard, "Zinc Oxide (Indirect Method)". Major domestic manufacturers include Shandong Xingyuan Zinc Industry Technology Co., Ltd., and Yangzhou Zhenzhong Zinc Industry Co., Ltd.
[0087] 5. Magnesium oxide Magnesium oxide (MgO) for the rubber industry is a light magnesium oxide with a content of ≥92%, which has both activating and acid-absorbing functions in the chloroprene rubber vulcanization system. It conforms to the HG / T2573-2012 standard, "Industrial Light Magnesium Oxide". Major domestic manufacturers include Hebei Magnesium God Technology Co., Ltd., and Shandong Lubei Chemical Co., Ltd.
[0088] 6. Sulfur Sulfur used in the rubber industry is insoluble sulfur or ordinary sulfur with a content of ≥99.5%, and is used as a vulcanization crosslinking agent. It complies with the GB / T2449-2006 standard "Industrial Sulfur".
[0089] 7. Stearic acid Stearic acid for the rubber industry is a white granular substance with an iodine value ≤8. It is used as a processing aid and vulcanization activator. It conforms to the GB9103-2013 standard "Industrial Stearic Acid".
[0090] 8. Aromatic softening oil Aromatic softening oil is an aromatic oil used in the rubber industry. It has a high aromatic hydrocarbon content (≥70%) and is used as a rubber plasticizer and softener to improve the processing flowability and flexibility of rubber compounds. It complies with the NB / SH / T0985-2019 standard "Rubber Filler Oil".
[0091] 9. Antioxidant 4020 (6PPD) Antioxidant 4020, chemically known as N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, is a p-phenylenediamine-based rubber antioxidant with excellent resistance to thermo-oxidative aging, ozone aging, and flexural cracking. Major domestic manufacturers include Yuncheng Jinteng Chemical Technology Co., Ltd. (designed capacity of 40,000 tons), Shandong Sider Chemical Technology Co., Ltd., Jiangsu Longda Chemical Co., Ltd., and Ningbo Haili Chemical Co., Ltd.
[0092] 10. Antioxidant RD (TMQ) Antioxidant RD, chemically named 2,2,4-trimethyl-1,2-dihydroquinoline polymer, is a quinoline-based rubber antioxidant with excellent thermal stability, suitable for long-term high-temperature aging conditions. When used in combination with antioxidant 4020, it produces a synergistic anti-aging effect. Major domestic manufacturers produce antioxidant 4020.
[0093] 11. Dispersant Dispersants used in the rubber industry are fatty acid esters or soap surfactants, used to improve the dispersion uniformity of fillers such as carbon black and silica in the rubber matrix and prevent filler agglomeration.
[0094] 12. Anti-flexural cracking agent PL-6000 PL-6000, an anti-flexural cracking additive, is a rubber-specific anti-fatigue functional additive, belonging to the anti-flexural cracking agent category within rubber protective additives. Commercially available rubber additive suppliers can provide similar functional additive products.
[0095] II. Sources of Main Production Equipment The production equipment used in this invention are all general-purpose equipment in the rubber processing industry and can be purchased through the following channels, but are not limited to the manufacturers listed: 1. Closed-type internal mixer Closed-type internal mixers (also known as internal mixers) are mainly used for plasticizing and mixing rubber. Equipped with a closed mixing chamber, they can effectively control the mixing temperature and prevent compounding agents from flying away. The internal mixer used in this invention has a temperature control system to ensure that the mixing temperature is ≤110℃. Major domestic manufacturers include Qingdao Xincheng Yiming Rubber Machinery Co., Ltd., Wuxi Jixiang Rubber & Plastic Machinery Co., Ltd., Dongguan Zhenggong Electromechanical Equipment Technology Co., Ltd., and Qingdao Shunfuchang Rubber Machinery Manufacturing Co., Ltd.
[0096] 2. Open mixing mill (open mill) Open-face mixing mills are mainly used for hot refining, sheeting, breaking, plasticizing, and mixing of rubber. This invention uses an open-face mill for thin-sheet extrusion, with an adjustable roll gap of 1.5mm. Major domestic manufacturers use internal mixers.
[0097] 3. Flat vulcanizing machine Flat vulcanizing machines are used for compression vulcanization molding of rubber products. Vulcanization temperature (150–160℃) is provided by electric heating or steam heating, and vulcanization pressure (15MPa) is provided by a hydraulic system. Major domestic manufacturers include Qingdao Xincheng Yiming Rubber Machinery Co., Ltd., Wuxi Jixiang Rubber & Plastic Machinery Co., Ltd., Qingdao Shunfuchang Rubber Machinery Manufacturing Co., Ltd., and Tiantai Yinlian Rubber Machinery Co., Ltd.
[0098] 4. Rubber flexural crack testing machine The Demesia type rubber flexural cracking tester is used to determine the flexural cracking properties of vulcanized rubber according to GB / T13934-2006 standard. It features frequency and stroke adjustment functions (5Hz frequency, 25mm stroke). Major domestic manufacturers include Jiangdu Xinzhenwei Testing Machinery Co., Ltd. and Jiangsu Mingzhu Testing Machinery Co., Ltd.
[0099] 5. Electronic universal tensile testing machine The electronic universal tensile testing machine is used to test the tensile strength, elongation at break, and stress at a given elongation of rubber according to the GB / T528 standard. It is equipped with pneumatic clamps and an extensometer. Major domestic manufacturers include MTS Industrial Systems (China) Co., Ltd., Shenzhen Xin Sansi Materials Testing Co., Ltd., and Zhuhai Sansi Taijie Electrical Equipment Co., Ltd.
[0100] 6. Shore A hardness tester The Shore A hardness tester is used to determine the Shore A hardness of rubber samples according to GB / T531.1 standard. Major domestic manufacturers include Shanghai Liuling Instrument Factory and Wenzhou Shandu Instrument Co., Ltd.
[0101] 7. Rubber Compression Set Tester The rubber compression set tester is used to determine the permanent deformation properties of rubber under compression according to the GB / T7759 standard. It consists of a compression clamp, a limiter, and a constant temperature chamber. Major domestic manufacturers include Jiangdu Zhenwei Testing Machinery Co., Ltd. and Jiangsu Mingzhu Testing Machinery Co., Ltd.
[0102] 8. Aging test chamber The aging test chamber is a thermo-oxidative aging test chamber used for accelerated aging tests of rubber samples in hot air (120℃×72h) according to GB / T3512 standard. It has precise temperature control (temperature fluctuation ≤±1℃). Major domestic manufacturers include Shanghai Yiheng Scientific Instruments Co., Ltd. and Chongqing Yinhe Test Instruments Co., Ltd.
[0103] 9. Thickness calipers and electronic analytical balance Thickness calipers are used to measure the thickness of rubber test pieces (accuracy 0.01 mm), and electronic analytical balances are used to accurately weigh each formulation component (accuracy 0.01 g). Both are general laboratory measuring devices.
[0104] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A type of base adhesive for transmission belts resistant to repeated flexural fatigue, characterized in that, By weight, it consists of the following components: 100 parts of chloroprene rubber CR121, 35-45 parts of high abrasion-resistant carbon black N330, 10-20 parts of silica, 4-6 parts of zinc oxide, 3-5 parts of magnesium oxide, 0.8-1.5 parts of sulfur, 0.5-2 parts of stearic acid, 3-7 parts of aromatic softening oil, 1.0-2.0 parts of antioxidant 4020, 0.5-1.5 parts of antioxidant RD, 0.5-2 parts of dispersant, and 2-5 parts of anti-flexural cracking agent PL-6000.
2. The transmission belt base adhesive resistant to repeated flexural fatigue according to claim 1, characterized in that, By weight, it consists of the following components: 100 parts of chloroprene rubber CR121, 40 parts of high abrasion-resistant carbon black N330, 15 parts of silica, 5 parts of zinc oxide, 4 parts of magnesium oxide, 1.0 part of sulfur; 1 part of stearic acid, 5 parts of aromatic softening oil, 1.5 parts of antioxidant 4020, 1 part of antioxidant RD, 1 part of dispersant, and 3 parts of anti-flexural cracking agent PL-6000.
3. The transmission belt base adhesive resistant to repeated flexural fatigue according to claim 1, characterized in that, The mass ratio of the high abrasion-resistant carbon black N330 to silica is 2 to 4:
1.
4. The transmission belt base adhesive resistant to repeated flexural fatigue according to claim 1, characterized in that, The mass ratio of antioxidant 4020 to antioxidant RD is 1 to 2:
1.
5. A transmission belt base adhesive resistant to repeated flexural fatigue according to any one of claims 1 to 4, characterized in that, The total mass of high abrasion-resistant carbon black N330 and silica in the primer is 50-60 parts, and silica accounts for 20%-35% of the total mass of the reinforcing filler system.
6. A transmission belt base adhesive resistant to repeated flexural fatigue according to any one of claims 1 to 4, characterized in that, The mass ratio of the anti-flexural cracking additive PL-6000 to silica is 1:3 to 8.
7. A method for preparing a transmission belt base adhesive resistant to repeated flexural fatigue as described in any one of claims 1 to 6, characterized in that, Includes the following steps: Step (1) First stage of intensive mixing: put chloroprene rubber into a closed intensive mixer and plasticize at room temperature for 2 minutes; add stearic acid, dispersant and antioxidant in sequence and mix for 3 minutes; then add carbon black, silica and softening oil in batches and continue mixing for 6-8 minutes, controlling the intensive mixing temperature ≤110℃. Step (2) Second stage reinforcement mixing: Discharge the first stage of the mixed rubber compound and let it stand and cool to room temperature. Then put it back into the internal mixer, add zinc oxide and magnesium oxide, mix for 3 minutes, and discharge the rubber compound. Step (3) Thin sheeting: Put the mixed rubber compound into the open mill, adjust the roller gap to 1.5mm, and repeat the thin sheeting 6 times, then make a triangular wrap and roll the roller 3 times each. Step (4) Curing: After filming, let it stand at room temperature for 24 hours to cure; Step (5) Compression vulcanization molding: Cut the cured rubber into shape and put it into a flat vulcanizing machine. The vulcanization temperature is 150-160℃, the vulcanization pressure is 15MPa, and the vulcanization time is 15-20min.
8. The method for preparing a transmission belt base adhesive resistant to repeated flexural fatigue according to claim 7, characterized in that, The total duration of the intensive mixing process in step (1) is 11 to 13 minutes.
9. The method for preparing a transmission belt base adhesive resistant to repeated flexural fatigue according to claim 7, characterized in that, In step (5), the vulcanization temperature is 155℃ and the vulcanization time is 18min.
10. The method for preparing a transmission belt base adhesive resistant to repeated flexural fatigue according to claim 7, characterized in that, In step (1), during the first stage of intensive mixing, carbon black and silica are added alternately in 2 to 3 batches, with an interval of 1 to 2 minutes between each batch.